2019
DOI: 10.1158/1078-0432.ccr-18-0432
|View full text |Cite
|
Sign up to set email alerts
|

CAR T Cells Targeting B7-H3, a Pan-Cancer Antigen, Demonstrate Potent Preclinical Activity Against Pediatric Solid Tumors and Brain Tumors

Abstract: Purpose: Patients with relapsed pediatric solid tumors and CNS malignancies have few therapeutic options and frequently die of their disease. Chimeric antigen receptor (CAR) T cells have shown tremendous success in treating relapsed pediatric acute lymphoblastic leukemia, but this has not yet translated to treating solid tumors. This is partially due to a paucity of differentially expressed cell surface molecules on solid tumors that can be safely targeted. Here, we present B7-H3 (CD276) as a putative target f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
463
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(479 citation statements)
references
References 55 publications
14
463
0
2
Order By: Relevance
“…This is in contrast to the B7-H3 CAR, which is unable to significantly produce IFNÎł or IL-2 in response to target cells expressing ~ 50,000 B7-H3 molecules/cell, while CARs targeting CD19, CD22, anaplastic lymphoma kinase (ALK), and CD30 demonstrated antigen density thresholds between those of CD20 and B7-H3 CARs. [72][73][74][75][76] Importantly, these antigen thresholds not only affect in vitro functions, but also impact in vivo efficacy, as has been demonstrated in preclinical models using the CD22, B7-H3, and ALK CARs. 72,74,75 From such observations, it is evident that the inability of CARs to respond to low levels of antigen represents an obstacle to current and future CAR T cell therapy.…”
Section: Anti G En Low E Sc Ape and C Ar T Cell Ac Tivati Onmentioning
confidence: 94%
See 2 more Smart Citations
“…This is in contrast to the B7-H3 CAR, which is unable to significantly produce IFNÎł or IL-2 in response to target cells expressing ~ 50,000 B7-H3 molecules/cell, while CARs targeting CD19, CD22, anaplastic lymphoma kinase (ALK), and CD30 demonstrated antigen density thresholds between those of CD20 and B7-H3 CARs. [72][73][74][75][76] Importantly, these antigen thresholds not only affect in vitro functions, but also impact in vivo efficacy, as has been demonstrated in preclinical models using the CD22, B7-H3, and ALK CARs. 72,74,75 From such observations, it is evident that the inability of CARs to respond to low levels of antigen represents an obstacle to current and future CAR T cell therapy.…”
Section: Anti G En Low E Sc Ape and C Ar T Cell Ac Tivati Onmentioning
confidence: 94%
“…[72][73][74][75][76] Importantly, these antigen thresholds not only affect in vitro functions, but also impact in vivo efficacy, as has been demonstrated in preclinical models using the CD22, B7-H3, and ALK CARs. 72,74,75 From such observations, it is evident that the inability of CARs to respond to low levels of antigen represents an obstacle to current and future CAR T cell therapy. Strategies have evolved to immediately overcome the problem of insensitivity to low levels of antigen by modulating the level of antigen expression on the malignant cells.…”
Section: Anti G En Low E Sc Ape and C Ar T Cell Ac Tivati Onmentioning
confidence: 94%
See 1 more Smart Citation
“…An analysis on the TCGA database showed that B7‐H3 expression is up‐regulated particularly in high‐grade gliomas . Majzner and colleagues developed a CAR‐targeting B7‐H3, showing preclinical anti‐tumor activity against multiple types of pediatric tumors including medulloblastoma, indicating potential clinical application of B7‐H3‐CAR T cells against certain types of brain tumors.…”
Section: Overcoming Tumor Heterogeneitymentioning
confidence: 99%
“…82,83 Careful selection and design of CAR T-cell constructs may potentially alleviate some of the issues associated with differences in antigen expression between healthy and tumor tissues. A recent study by Majzner et al 84 demonstrated that CAR T cells targeting the pan-cancer antigen B7-H3 mediated cytolysis of high antigen-expressing tumor cells whilst displaying minimal reactivity towards low antigen-expressing cells. This suggests that antigens that are found on normal tissues may still serve as safe targets, provided that their expression on tumor cells is sufficiently distinguishable by CAR T cells.…”
Section: Car T Cells Targeting Intracellular Tumor Antigensmentioning
confidence: 99%